THE ROLE OF POLITENESS IN PROFESSIONAL COMMUNICATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the importance of communication culture and the principles of politeness in professional activity. It analyzes the impact of adhering to ethical norms on work efficiency, as well as its role in creating a healthy environment within a team. As a result of the research, the key aspects of politeness in professional communication and its role in society are highlighted.